1990
DOI: 10.1056/nejm199009133231103
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory and Antimicrobial Efficacy of Intravenous Immunoglobulin in Bone Marrow Transplantation

Abstract: Passive immunotherapy with intravenous immunoglobulin decreases the risk of acute GVHD, associated interstitial pneumonia, and infections after bone marrow transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
119
2
14

Year Published

1992
1992
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 372 publications
(137 citation statements)
references
References 54 publications
2
119
2
14
Order By: Relevance
“…12 Although some studies show that IVIG reduce GvHD and mortality, many others fail to demonstrate the same effect. [14][15][16][17][18] As reviewed by Sokos et al, 12 IVIG were shown to be efficient in reducing GvHD in only three 13,44,45 of eight studies [13][14][15][16][17][18]44,45 that together comprised of 2507 patients. Determining the true effect of IVIG in these clinical studies is a key challenge as it is difficult to derive quality data from comparisons of heterogenous stages of pathology and treatment regimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Although some studies show that IVIG reduce GvHD and mortality, many others fail to demonstrate the same effect. [14][15][16][17][18] As reviewed by Sokos et al, 12 IVIG were shown to be efficient in reducing GvHD in only three 13,44,45 of eight studies [13][14][15][16][17][18]44,45 that together comprised of 2507 patients. Determining the true effect of IVIG in these clinical studies is a key challenge as it is difficult to derive quality data from comparisons of heterogenous stages of pathology and treatment regimens.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by the current status of IVIG as an approved therapy for GvHD prophylaxis, although many authors question their utility. 12 On one hand, Sullivan et al 13 showed in a randomized trial that weekly IVIG reduced the cumulative incidence of acute GvHD and that this effect was significant in patients receiving HLA-identical HSCT. Also, in patients older than 20 years receiving HLA-identical HSCT, the incidence of non-relapse mortality was significantly less in patients receiving IVIG.…”
Section: Introductionmentioning
confidence: 99%
“…3,[6][7][8][9][10][11] In a randomized prospective trial of 382 patients (30% were o20 years of age), the patients received 500 mg/kg weekly IVIG infusions until day 90 and then monthly until 1 year were compared with the control group. 10 The control group had a significantly higher risk of Gramnegative systemic infections, as well as local infections. Among patients X20 years of age, there was an increased risk of acute GVHD and an increased TRM.…”
Section: Discussionmentioning
confidence: 99%
“…Passive immunotherapy with intravenous immunoglobulins decreases not only incidence of interstitial pneumonia and the severity of infections but also the risk of acute GVHD. 38 Bacterial endotoxins can activate cells of the monocyte macrophage system and lead to subsequent release of interleukin-1 and tumor-necrosis factor (TNF), known to enhance T cell proliferation. Endotoxin lipopolysaccharide in the cell wall of gram-negative bacteria can enter the circulation after disruption of the mucosal barrier, and can accumulate in the blood in cases of impaired hepatic clearance.…”
Section: Discussionmentioning
confidence: 99%